Genetic analysis of polyomavirus large T nuclear localization: nuclear localization is required for productive association with pRb family members. - Howes, S H (1996)
Polyomavirus large T antigen (LT) is a multifunctional nuclear protein. LT has two nuclear localization signals (NLS2), one spanning residues 189 to 195 (NLS1) and another spanning residues 280 to 286 (NLS2). Site-directed mutagenesis showed that each signal contains at least two critical residues. The possibility of connections between NLSs and adjacent phosphorylations has attracted much attention. Cytoplasmic LT (CyT) mutants were underphosphorylated, particularly at sites adjacent to NLS2. However, since a nuclear LT bearing an inactivated NLS2 was phosphorylated normally at adjacent sites, the signal was not directly required for phosphorylation. Conversely, LT could be translocated to the nucleus via NLS2 even when the adjacent phosphorylation sites were deleted. CyT was examined to probe the importance of LT localization. CyT was unable to perform LT functions related to interactions with retinoblastoma susceptibility gene (pRb) family members. Hence, CyT was unable to immortalize primary cells or to transactivate an E2F-responsive promoter. Consistent with these findings, CyT, though capable of binding pRb in vitro, did not cause relocalization of pRb in cells. Assays of transactivation of the simian virus 40 late promoter and of the human c-fos promoter showed that defects of CyT were not limited to functions dependent on pRb interactions.